Applying the revenge system to the criminal justice system and jury decision-making - Murray, Jennifer (2013)
McCullough et al. propose an evolved cognitive revenge system which imposes retaliatory costs on aggressors. They distinguish between this and other forms of punishment (e.g., those administered by judges) which are not underpinned by a specifically designed evolutionary mechanism. Here we outline mechanisms and circumstances through which the revenge system might nonetheless infiltrate decision-making within the criminal justice system